Metasurface cut-off absorber based on nanometer cross-shaped structure
By designing an assembly array composed of nanocross-shaped structures and nanorings in a metasurface absorber, the size of Si and GaAs nanostructures is optimized, and high absorption and cutoff efficiency in the 200-690nm wavelength band is achieved, and the current solution is to solve the problem. There are problems of low absorption efficiency and narrow bandwidth in the technology, which significantly improves cutoff efficiency and absorption characteristics.
Patent Information
- Application Number
- CN202411622845.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2024-12-13
AI Technical Summary
When existing metasurface absorbers achieve perfect cutoff and absorption of light, there are problems of low absorption efficiency, narrow bandwidth and large volume. Especially in application scenarios where it is necessary to clearly distinguish between absorption and non-absorbing belts, cutoff efficiency is difficult. promote.
Using a metasurface cut-off absorber based on a nanocross-type structure, the assembly array composed of nanocross and nanorings is grown on a silica substrate, using Si and GaAs as absorbing materials to achieve high structure and size optimization Absorption efficiency and cutoff efficiency, specific parameters include the size of Si nanocrosses and GaAs nanocrosses and the design of GaAs nanorings, and are optimized in combination with the time-domain finite difference method.
A high absorption rate was achieved in the 200-690nm wavelength band (average 0.967), with a sharp drop from the 690nm wavelength to 0.095 at the 940nm wavelength band. The average absorption rate in the 940-20000nm band is only 0.012, and the extinction ratio ER It is 9.725dB, the extinction difference ED is 0.793, and the cutoff slope CS is 0.233 nm-1, which significantly improves the cutoff efficiency and absorption characteristics.
Smart Images

Figure CN119126276A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of optical metamaterials, and in particular to a cutoff absorber. Background Art
[0002] Metamaterials are composed of a series of carefully arranged subwavelength engineering structures, which exhibit unique electromagnetic phenomena and physical properties that many natural materials do not have, and are widely used in antenna design, stealth technology, solar cells, sensors and other fields. In recent years, with the rapid development of optical technology, the precise control of light has become a research hotspot. Traditional absorption materials often have problems such as low absorption efficiency, narrow bandwidth, and large size. Metamaterials, as a kind of material, have demonstrated excellent optical performance control capabilities by precisely controlling the interaction between light and matter. However, existing metasurface absorbers still face many challenges in specific application scenarios, such as when perfect cutoff and absorption of light are required.
[0003] In many applications, a clear absorption cutoff is required between the absorption band and the non-absorption band. The cutoff absorption efficiency can be expressed as the extinction ratio ER = 10*log (Aa / An) dB, where Aa is the minimum absorption in the absorption band and An is the maximum absorption in the non-absorption band; the extinction difference ED = Aa-An; the cutoff slope CS = (Aa-An) / (λa-λn), where λa is the maximum wavelength / minimum wavelength in the absorption band and λn is the minimum wavelength / maximum wavelength in the non-absorption band. Ideally, ER, ED, and CS should be as large as possible; these works have made great progress in the field of broadband absorbers, but they did not consider the cutoff efficiency, which is important in applications. Summary of the invention
[0004] In view of the shortcomings in the prior art, the present invention provides a metasurface cutoff absorber based on a nano-cross structure, which provides an effective method for filtering light with a wavelength below 940nm to obtain IPL.
[0005] The objective of the present invention is achieved in this way: a supersurface cutoff absorber based on a nano-cross structure comprises a thin film grown on a silicon dioxide substrate, an assembly array composed of nano-crosses and nano-rings is arranged on the thin film, a single nano-cross and a single nano-ring form a single assembly, and a plurality of assemblies form an array; the nano-cross comprises a Si nano-cross formed on the thin film and a GaAs nano-cross formed on the Si nano-cross, the nano-ring is a GaAS nano-ring, and the GaAS nano-ring surrounds the GaAs nano-cross.
[0006] Furthermore, the substrate is square, the thin film is uniformly grown on the substrate, and the side length is consistent with the array period P.
[0007] Furthermore, the film is a square aluminum film, and the side length of the aluminum film is consistent with the array period.
[0008] Furthermore, the height of the Si nano cross is h1=50-60nm, the length is w1=200-220nm, and the width is w1=20-25nm.
[0009] Furthermore, the height of the GaAs nano cross is h2=100-110nm, the length is l2=245-250nm, and the width is w2=30-35nm.
[0010] Furthermore, the height of the GaAs nano-ring is h3=75-80nm, the outer ring radius is r1=142-146nm, and the inner ring radius is r2=126-136nm.
[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: the average absorption of the present invention in the wavelength band (absorption band) between 200-690nm is 0.967, the absorption drops sharply from 0.941 at the wavelength of 690nm to 0.095 at the wavelength of 940nm, and the average absorption rate in the non-absorption band of 940-20000nm is only 0.012; wherein the extinction ratio ER is 9.725dB, the extinction difference ED is 0.793, and the cut-off slope CS is 0.233nm -1 ; In the structure, silicon dioxide serves as the base support structure, and aluminum serves as a reflective layer to prevent light projection; both silicon and gallium arsenide serve as absorption materials, and by changing their structure and size, resonance in a specific band is achieved to produce high absorption; in other bands, since their parameters do not meet the resonance conditions, strong resonance cannot be achieved, and high absorption cannot be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0013] Figure 1 This is a schematic diagram of the structure of the supersurface cutoff absorber of the present invention.
[0014] Figure 2 It is a cross-sectional view of a single assembly in the present invention.
[0015] Figure 3 is the theoretical value of the absorption spectrum of the perfect absorber in the wavelength range of 200-20000 nm in the present invention, and the light is incident along the -Z direction.
[0016] Figure 4 is the theoretical value of the absorption spectrum of the perfect absorber in the wavelength range of 200-4000 nm in the present invention, and the light is incident along the -Z direction.
[0017] Figure 5 Schematic diagram of the effect of parameter P on overall absorption in the present invention.
[0018] Figure 6 Schematic diagram of the effect of parameter l1 on overall absorption in the present invention.
[0019] Figure 7 Schematic diagram of the effect of parameter w1 on overall absorption in the present invention.
[0020] Figure 8 Schematic diagram of the effect of parameter l2 on overall absorption in the present invention.
[0021] Fig. 9 Schematic diagram of the effect of parameter w2 on overall absorption in the present invention.
[0022] Fig.10 Schematic diagram of the effect of parameter r1 on overall absorption in the present invention.
[0023] Fig.11 Schematic diagram of the effect of parameter r2 on overall absorption in the present invention.
[0024] Fig.12 Schematic diagram of the effect of parameter h1 on overall absorption in the present invention.
[0025] Fig.13 Schematic diagram of the effect of parameter h2 on overall absorption in the present invention.
[0026] Fig.14 Schematic diagram of the effect of parameter h3 on overall absorption in the present invention.
[0027] Fig.15 Schematic diagram of the effect of parameter h4 on overall absorption in the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] like Figure 1-2A metasurface cutoff absorber based on a nano-cross structure is shown, wherein a uniform aluminum film is covered on a SiO2 substrate, the side length of which is consistent with the array period P and the thickness is h4; a Si nano-cross is uniformly epitaxially grown on the aluminum film, and a GaAs nano-cross is embedded in the center of the Si nano-cross to form an assembly, and a GaAS nano-ring is placed to surround the GaAs nano-cross to form an array structure; wherein the height of the Si nano-cross is h1, the length is 11, and the width is w1; the height of the GaAs nano-cross is h2, the length is l2, and the width is w2; the height of the GaAs nano-ring is h3, the outer ring radius is r1, and the inner ring radius is r2.
[0030] The cutoff perfect absorber proposed in the present invention is calculated and optimized using the finite difference time domain method (FDTD). The parameter optimization range is r1=142-146nm, r2=126-136nm, h1=50-60nm, h2=100-110nm, h3=75-80nm, h4=50-60nm, l1=200-220nm, l2=245-250nm, w1=20-25nm, w2=30-35nm, P=287-292nm; Figure 3-4 It reflects the theoretical value of the absorption spectrum under the optimal parameters. At this time, the optimal parameter values are: r1=142nm, r2=136nm, h1=60nm, h2=100nm, h3=75nm, h4=60nm, 11=220nm, 12=245nm, w1=20nm, w2=30nm, P=292nm.
[0031] Figure 3 The absorption spectrum theoretical value of the optimized structure is shown. The average absorption in the wavelength band (absorption band) between 200-690nm is 0.967, and the absorption drops sharply from 0.941 at 690nm to 0.095 at 940nm. The average absorption rate in the non-absorption band of 940-20000nm is only 0.012. The extinction ratio ER is 9.725dB, the extinction difference ED is 0.793, and the cutoff slope CS is 0.233 nm -1 In the structure, silicon dioxide is used as the base support structure, and aluminum is used as a reflective layer to prevent light projection. Silicon and gallium arsenide are both used as absorption materials. By changing their structure and size, resonance in a specific band is achieved to produce high absorption. In other bands, since their parameters do not meet the resonance conditions, strong resonance cannot be achieved, and high absorption cannot be achieved.
[0032] The finite-difference time-domain (FDTD) method is used below to study the physical mechanism of cutoff perfect absorption in the cutoff perfect absorber, explore the allowable range of parameter errors in actual manufacturing production, and use the control variable method to change each geometric parameter in turn to study the influence of different geometric parameters on the working performance of the absorber.
[0033] When other simulation parameters remain unchanged, as the array period P changes, the change process of the structure's absorption rate of incident light is as follows: Figure 5 The simulation range set by the present invention is from 287nm to 322nm, and the simulation step is 5nm. Figure 5 It can be seen that when the period P = 287nm, the absorption in the absorption band is higher, with an average absorption of 0.936. When the period P = 292nm, the absorption of the absorption band is further improved, with an average absorption of 0.969. When the P value is further increased from 297nm to 322nm, the average absorption rate of the absorption band is between 0.880 and 0.963, which is lower than 0.969. Therefore, in order to simultaneously maintain high absorption in the absorption band, the present invention sets P = 292nm in the cutoff perfect absorber.
[0034] When other simulation parameters remain unchanged, as the length l1 changes, the change process of the structure's absorption rate of incident light is as follows: Figure 6 The simulation range set by the present invention is from 180nm to 250nm, and the simulation step is 10nm. Figure 6 It can be seen that when the length l1=180nm, the average absorptivity of the absorption band is 0.971, and its absorption band is 220-690nm. When the length l1 increases to 190nm, the average absorptivity of the absorption band is 0.965, which decreases slightly, and the absorption band still remains at 220-690nm. When l1=180nm, the average absorptivity increases to 0.969, and its absorption band widens to 210-690nm. As the length l1 further increases from 200nm to 250nm, the average absorptivity of its absorption band is between 0.947 and 0.964, and at l1=220nm, the maximum average absorptivity is obtained, and its absorptivity is 0.964, and its absorption band widens to 200-690nm. Therefore, in order to simultaneously maintain high absorption in the absorption band and a wider absorption band, the present invention sets the length l1=220nm.
[0035] When other simulation parameters remain unchanged, as the width w1 changes, the change process of the structure's absorption rate of incident light is as follows: Figure 7 The simulation range set by the present invention is from 5nm to 25nm, and the simulation step is 5nm. Figure 7It can be seen that when w1=5nm, its absorption band is 220-530nm, and the average absorptivity of its absorption band is 0.963. As w1 increases from 10nm to 15nm, its absorption band widens to 200-560nm, and the average absorptivity of its absorption band is 0.966. As w1 increases from 20nm to 25nm, its absorption band widens to 200-690nm, and the average absorptivity of its absorption band is 0.964. Although when w1=20nm, its average absorptivity is 0.964, which is slightly lower than 0.966, its absorption band width is greatly widened. Therefore, in order to simultaneously maintain high absorption in the absorption band and a wider absorption band, the present invention sets the width w1=20nm. It is worth noting that the present invention sets w1 to 20nm instead of 25nm here because when w1=25nm, the width and average absorptivity of its absorption band are consistent with w1=20nm. Therefore, the present invention sets w1=20 nm to save materials, which is an advantage in manufacturing devices.
[0036] When other simulation parameters remain unchanged, as the length l2 changes, the change process of the structure's absorption rate of incident light is as follows: Figure 8 The simulation range set by the present invention is from 230nm to 265nm, and the simulation step is 5nm. Figure 8 It can be seen that as the length l2 increases from 230nm to 250nm, the average absorptivity of the absorption band continues to increase, and the maximum value of 0.966 is obtained at l2=245nm. As the length l2 increases from 255nm to 265nm, the average absorptivity of the absorption band continues to decrease, with a minimum of 0.847. Therefore, in order to maintain high absorption in the absorption band, the present invention sets the length l2=245nm. Similar to the previous case, the present invention sets l2 to 245nm instead of 250nm because when l2=250nm, the width and average absorptivity of its absorption band are consistent with l2=245nm. Therefore, the present invention sets l2=245nm to save materials, which is an advantage when manufacturing devices.
[0037] When other simulation parameters remain unchanged, as the width w2 changes, the change process of the structure's absorption rate of incident light is as follows: Fig. 9 The simulation range set by the present invention is from 25nm to 55nm, and the simulation step is 5nm. Fig. 9It can be seen that as the length w2 increases from 25nm to 35nm, the average absorptivity of the absorption band increases continuously, and the maximum value of 0.966 is obtained when w2=30nm. As the length w2 increases from 40nm to 55nm, the average absorptivity of the absorption band decreases continuously, and the minimum is 0.948. Therefore, in order to maintain high absorption in the absorption band, the present invention sets the width w2=30nm. The present invention sets w2 to 30nm instead of 35nm, which is still out of consideration of saving materials, and will not be repeated here.
[0038] When other simulation parameters remain unchanged, as the outer diameter r1 of the ring changes, the absorptivity of the structure to the incident light changes as shown in the following figure: Fig.10 The simulation range set by the present invention is from 140nm to 146nm, and the simulation step is 1nm. Fig.10 It can be seen that when the outer diameter r1=140nm, its absorption band is 330-690nm, and the average absorptivity of the absorption band is 0.968. In the process of r1 increasing from 141nm to 146nm, the average absorptivity of the absorption band is between 0.936-0.966, and the maximum average absorptivity is 0.966 when r1=142nm. When r1=142nm, although the average absorptivity of its absorption band is slightly lower than 0.968, its absorption band extends to 200-690nm, which is greatly improved. Therefore, in order to simultaneously maintain the high absorption and wide absorption bandwidth of the absorption band, the present invention sets the outer diameter r1=142nm.
[0039] When other simulation parameters remain unchanged, as the inner diameter r2 of the ring changes, the change process of the structure's absorption rate of incident light is as follows: Fig.11 As shown. The simulation range set by the present invention is from 126nm to 138nm, and the simulation step size is 2nm. As r2 continues to grow from 126nm to 136nm, the average absorptivity of the absorption band continues to increase, and obtains a maximum value when r2=136nm, and the maximum value is 0.966. When r2 further grows to 138nm, the average absorptivity of the absorption band increases to 0.977, but its absorption band is reduced to 340-690nm, and the absorption band is 200-690nm when r2=136nm. Obviously, although there is a maximum average absorptivity when r2=138nm, it is very wasteful to sacrifice the bandwidth of 140nm. Therefore, in order to simultaneously maintain the high absorption and wide absorption bandwidth of the absorption band, the present invention sets the inner diameter r2=136nm.
[0040] When other simulation parameters remain unchanged, as the height h1 changes, the change process of the structure's absorption rate of incident light is as follows: Fig.12As shown. The simulation range set by the present invention is from 30nm to 90nm, and the simulation step is 10nm. As h1 increases from 30nm to 60nm, the average absorptivity of the absorption band increases continuously, and a maximum value of 0.966 is obtained when h1=60nm. As h1 increases from 70nm to 90nm, the average absorptivity of the absorption band decreases continuously, and the minimum value is 0.955. Therefore, in order to maintain the high absorption of the absorption band, the present invention sets the height h1=60nm.
[0041] When other simulation parameters remain unchanged, as the height h2 changes, the change process of the structure's absorption rate of incident light is as follows: Fig.13 As shown. The simulation range set by the present invention is from 90nm to 150nm, and the simulation step size is 10nm. When h2=90nm, its absorption band is 220-690nm, and the average absorptivity of the absorption band is 0.967. When h2 increases to 100nm, its absorption band expands to 200-690nm, and the average absorptivity of the absorption band is 0.966. Although the average absorptivity is slightly reduced, the average absorptivity of the absorption band is improved. As h2 continues to grow from 110nm to 150nm, the average absorptivity of the absorption band is between 0.951-0.966, none of which exceeds 0.966, and the bandwidth of the absorption band does not exceed 490nm. Therefore, in order to simultaneously maintain the high absorption and wider absorption band of the absorption band and save materials, the present invention sets the height h2=100nm.
[0042] When other simulation parameters remain unchanged, as the height h3 changes, the change process of the structure's absorption rate of incident light is as follows: Fig.14 As shown. The simulation range set by the present invention is from 60nm to 90nm, and the simulation step size is 5nm. When h3=60nm, its absorption band is 240-690nm, and the average absorptivity of the absorption band is 0.971. When h3 further increases to 65nm, its absorption band is still 240-690nm, but the average absorptivity of its absorption band increases to 0.972. As h3 increases from 70nm to 90nm, its absorptivity is between 0.961-0.967, and a maximum value of 0.967 is obtained at h3=75nm. Although the average absorptivity of its absorption band decreases compared to 0.972 when h3=75nm, its absorption band is extended to 200-690nm. Obviously, it is worthwhile to sacrifice an average absorptivity of 0.005 in exchange for an absorption bandwidth of 40nm. Therefore, in order to simultaneously maintain the high absorption and wide absorption bandwidth of the absorption band, the present invention sets the height h3=75nm.
[0043] When other simulation parameters remain unchanged, as the height h4 changes, the change process of the structure's absorption rate of incident light is as follows: Fig.15As shown. The simulation range set by the present invention is from 40nm to 100nm, and the simulation step size is 10nm. When h4=40nm, its absorption band is 230-690nm, and the average absorptivity of the absorption band is 0.970. As h4 continues to grow from 50nm to 80nm, its absorption band expands to 200-690nm, and the average absorptivity of the absorption band stabilizes at 0.967, which decreases slightly. As h4 grows from 90nm to 100nm, its absorption band is 200-690nm, remains unchanged, and the average absorptivity of its absorption band increases to 0.968, but at this time the non-absorption band is more oscillating. When h4=60nm, although the average absorptivity of its absorption band decreases slightly, its non-absorption band is relatively gentle. Therefore, in order to simultaneously maintain a higher absorption bandwidth and rapid convergence of the non-absorption band, the present invention sets the height h4=60nm.
[0044] In summary, the present invention designs a perfect cutoff absorber with a working band of 200-690nm, and the optimized parameters are as follows: the optimized structural parameter range is r1=142-146nm, r2=126-136nm, h1=50-60nm, h2=100-110nm, h3=75-80nm, h4=50-60nm, l1=200-220nm, l2=245-250nm, w1=20-25nm, w2=30-35nm, P=287-292nm. The absorber achieves an average absorptivity of 0.967 in the absorption band of 200-690nm, and the absorption drops sharply from 0.941 at a wavelength of 690nm to 0.095 at a wavelength of 940nm, and the average absorptivity in the non-absorption band of 940-20000nm is only 0.012. The extinction ratio ER is 9.725dB, the extinction difference ED is 0.793, and the cutoff slope CS is 0.233 nm. -1 .
[0045] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A metasurface cutoff absorber based on a nano-cross structure, characterized in that: The invention comprises a film grown on a silicon dioxide substrate, wherein an assembly array composed of nano crosses and nano rings is arranged on the film, a single nano cross and a single nano ring form a single assembly, and a plurality of assemblies form an array; the nano cross comprises a Si nano cross formed on the film and a GaAs nano cross formed on the Si nano cross, the nano ring is a GaAS nano ring, and the GaAS nano ring is arranged to surround the GaAs nano cross.
2. The metasurface cutoff absorber based on a nano-cross structure according to claim 1 is characterized in that: The substrate is square, and the thin film is uniformly grown on the substrate, and the side length thereof is consistent with the array period P.
3. A supersurface cutoff absorber based on a nano-cross structure according to claim 1 or 2, characterized in that: The film is a square aluminum film, and the side length of the aluminum film is consistent with the array period.
4. The metasurface cutoff absorber based on a nano-cross structure according to claim 1 or 2, characterized in that: The Si nano cross has a height of h1=50-60 nm, a length of w1=200-220 nm, and a width of w1=20-25 nm.
5. The metasurface cutoff absorber based on a nano-cross structure according to claim 1 or 2, characterized in that: The GaAs nano cross has a height of h2=100-110 nm, a length of l2=245-250 nm, and a width of w2=30-35 nm.
6. The metasurface cutoff absorber based on a nano-cross structure according to claim 1 or 2, characterized in that: The height of the GaAs nano-ring is h3=75-80nm, the radius of the outer ring is r1=142-146nm, and the radius of the inner ring is r2=126-136nm.
